Phytochemical Screening of Chloroform Extract from Javanese Long Pepper which Dried Through 2 Different Methods: Skrining Fitokimia Ekstrak Kloroform dari Buah Cabe Jawa yang Dikeringkan dengan 2 Metode Berbeda - Diah Wulan Safitri; Meyke Herina Syafitri (Akademi Farmasi Surabaya, 2022)
Fruit is easily damaged and has a short shelf life due to the high water content. Drying is one of the post-harvest handling processes that can reduce the water content of the product to increase stability during product distribution and storage. Javanese long pepper (Piper retrofractum Vahl.) is included in the 10 largest raw materials absorbed by the traditional medicine industry. Purpose of this study is to carry out phytochemical screening of chloroform extract from javanese long pepper which dried through 2 different methods. Group 1 was air-dried, while group II was pre-treated with blanching, which was boiled for a few minutes before drying in direct sunlight. The dried implicia produced from both groups were macerated with chloroform for 3 days each. The maceration filtrate then tested to determine the secondary metabolite compounds contained in it through phytochemical screening. The test is carried out by observing the presence or absence of a precipitate formed or the color change that occurs after the addition of reagents. The results showed that both groups were positive for alkaloids, flavonoids and steroids, but negative for terpenoids, tannins, and saponins. There was no difference in content between the two treatment groups.